The way of love a tribute to Saint Teresa of Calcutta - Roychowdhury, Satyam (Bee Books, 2017)
The way of love a tribute to Saint Teresa of Calcutta / Roychowdhury, Satyam. -- Kolkata: Bee Books, 2017 920 R888 No. of Copies : 2